Hallmarks of Anaplastic Lymphoma Kinase Inhibitors with Its Quick Emergence of Drug Resistance - Yong-Fu Qiu; Lian-Hua Song; Gang-Long Jiang; Zhen Zhang; Xu-Yan Liu; Guan Wang (Georg Thieme Verlag KG, 2022)
Abstract Anaplastic lymphoma kinase (ALK) is one of the most popular targets for anticancer therapies. In the past decade, the use of anaplastic lymphoma tyrosine kinase inhibitors (ALK-TKIs), including crizotinib and ceritinib, has been a reliable and standard options for patients with lung cancer, particularly for patients with nonsmall cell lung carcinoma. ALK-targeted therapies initially benefit the patients, yet, resistance eventually occurs. Therefore, resistance mechanisms of ALK-TKIs and the solutions have become a formidable challenge in the development of ALK inhibitors. In this review, based on the knowledge of reported ALK inhibitors, we illustrated the crystal structures of ALK, summarized the resistance mechanisms of ALK-targeted drugs, and proposed potential therapeutic strategies to prevent or overcome the resistance.